AI POWERED PERSONALIZATION IN MARKETING: BALANCING CUSTOMER ENGAGEMENT AND PRIVACY CONCERNS - Mulyono, Sri; Letsoin, Edward Kurniawan Saputra (Management Studies and Business Journal (PRODUCTIVITY), 2025)
The application of artificial intelligence (AI) in marketing strategies has increased rapidly, but there are significant concerns about data privacy that can erode consumer trust. This study aims to explore how AI-based personalization strategies can balance customer engagement and privacy concerns.This study focuses on developing a framework that integrates aspects of technology, consumer behavior, and privacy ethics in the context of digital marketing.This study used the Systematic Literature Review (SLR) approach with the PRISMA protocol to identify and analyze relevant literature. Data were collected from the Scopus and Web of Science databases, with thematic analysis to identify key patterns and themes.The findings suggest that transparency in data usage, user control over personal information, and application of data minimization principles are key strategies for building trust and increasing customer engagement. The study also identifies mediators such as trust and perceived risk that influence the relationship between AI personalization and privacy.These findings make a significant contribution to the development of digital marketing theory and offer practical guidance for marketers to design ethical and effective strategies, which can increase customer loyalty and strengthen long-term relationships.